Research Progress, Challenges, and Breakthroughs of Organoids as Disease Models - Huang, Yisheng; Huang, Zhijie; Tang, Zhengming; Chen, Yuanxin; Huang, Mingshu; Liu, Hongyu; Huang, Weibo; Ye, Qingsong; Jia, Bo (Frontiers in Cell and Developmental Biology, 2021)
Traditional cell lines and xenografts models have been widely recognized and used in various research. As a new research model, organoids have made significant progress and development in the past ten years. Compared with traditional models, organoids have more advantages and have been applied in cancer research, genetic diseases, infectious diseases, and regenerative medicine. In this review, we will show the advantages of organoids in the study of various diseases. It also summarizes that there are still defects in organoids and focuses on scientists' breakthroughs in vascularization, immune microenvironment, and hydrogel.